2020
DOI: 10.1111/1753-0407.13010
|View full text |Cite
|
Sign up to set email alerts
|

Insulin resistance is associated with urinary albumin‐creatinine ratio in normal weight individuals with hypertension and diabetes: The REACTION study

Abstract: Background: The relationship between albuminuria and insulin resistance (IR) has not been clarified in previous studies. This study was conducted to examine whether IR is associated with albuminuria in subjects with diverse blood pressure and glycometabolism statuses.Methods: This study included 34 136 participants whose data were drawn from a cross-sectional survey named the 2011 REACTION study. The participants were divided into six groups. The urinary albumin-creatinine ratio (UACR) and glomerular filtratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 29 publications
1
13
0
Order By: Relevance
“…Furthermore, a study from a sub-center of the REACTION study found that TG/HDL-C showed a more powerful association with elevated UACR compared with other lipid parameters Table 4 The logistic regression analyses evaluating the correlation between TG/HDL-C and increased UACR in subgroups [22]. However, the study did not carry out fully adjustments for confounders, including HOMA-IR, which was found to be closely related to both UACR [28] and TG/ HDL-C [17,18]. It is noteworthy that compared with the abovementioned studies, this study involved a larger general population from 7 regions of China and adjusted for extensive confounders, which ensured a preferable representation of the general population in China.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a study from a sub-center of the REACTION study found that TG/HDL-C showed a more powerful association with elevated UACR compared with other lipid parameters Table 4 The logistic regression analyses evaluating the correlation between TG/HDL-C and increased UACR in subgroups [22]. However, the study did not carry out fully adjustments for confounders, including HOMA-IR, which was found to be closely related to both UACR [28] and TG/ HDL-C [17,18]. It is noteworthy that compared with the abovementioned studies, this study involved a larger general population from 7 regions of China and adjusted for extensive confounders, which ensured a preferable representation of the general population in China.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies have observed that higher UACR levels in patients with hypertension and insulin resistance [ 24 , 25 ]. A study demonstrated that hypertension significantly increased protein excretion in urine and contributed to the development of nephropathy in diabetics [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…A lot of researches have presented that HOMA-IR is strongly associated with the progression of albuminuria. Recently, the REACTION (Risk Evaluation of Cancers in Chinese Diabetic Individuals: A Longitudinal) study conducted in China [ 23 ] found that HOMA-IR was positively related to UACR in prediabetes or diabetes groups, but this relationship was not found in the normal glucose tolerance group. Another large prospective study showed that HOMA-IR quintiles were correlated with the incidence of CKD in adults without diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated the associations between the two indexes mentioned above with microalbuminuria or CKD separately in specific populations, such as elderly individuals or those with diabetes [ 14 , 23 ]. However, this study compared the performance of TyG index with HOMA-IR in general population.…”
Section: Discussionmentioning
confidence: 99%